The solution of customs posts management problems at railway border stations - Jarašūnienė, Aldona (Transport, 2003)
The Identification and solution of transportation problems related to customs posts at railway border stations enable successful functioning of international freight transport, thus guaranteeing its reliability, punctuality and high quality. Perfection of the complex work is necessary in order to meet the requirements as well as to preserve goods during their transportation process. For the solution of the problems at the stations it is important to analyse fundamental principles, to assess an environmental impact, to formulate and evaluate the issues of wagon management by means of complicated technical systems, and to optimise the process of problems on the basis of research methods.First Published Online: 19 Dec 2011